Ethnic differences in the mother-son relationship of incarcerated and non-incarcerated male adolescents in the Netherlands - Pels Trees; Deković Maja; Doreleijers Theo AH; Stevens Gonneke WJM; Veen Violaine C; Vollebergh Wilma AM (BMC, 2011)
Abstract Background In the Netherlands, youths of Moroccan origin account for a disproportionately large percentage of the population in juvenile justice institutions. Previous research showed that Moroccan adolescents in pre-trial arrest are characterized by less serious offending behavior (i.e., primarily property-based) and lower levels of mental health problems than native Dutch adolescents in pre-trial arrest. To date, little is known about the parent-child relationship of these adolescents. This study examines the mother-son relationships of Moroccan and native Dutch delinquent adolescents and their association with adolescent delinquency. Methods In the present study, differences in the mother-son relationship characteristics between families of incarcerated (N = 129) and non-incarcerated (N = 324) adolescents were examined, and it was analyzed if these differences between incarcerated and non-incarcerated adolescents were the same for Moroccans and native Dutch. Data collection for the incarcerated sample took place from 2006 to 2008. Comparison data were used of interviews conducted with mothers originating from former larger studies in the general Dutch population. Latent Class Analysis was performed in order to identify types of mother-son relationship. Logistic regression analyses were used to identify the relationships between mother-son relationship types, incarceration and ethnicity. Results A three class model of mother-son relationship types was found: a low-conflict mother-son relationship type, a high-conflict mother-son relationship type, and a neglectful mother-son relationship type. Compared to the native Dutch adolescents, Moroccans (both in the incarcerated and non-incarcerated population) more often showed a neglectful mother-son relationship type. For Moroccans, no differences in mother-son relationship types were found between the incarcerated and non-incarcerated adolescents, whereas considerable differences occurred between the native Dutch incarcerated and non-incarcerated adolescents. Conclusions Our findings indicate that mother-son relationship types of incarcerated Moroccan adolescents and non-incarcerated Moroccan adolescents are rather comparable. These findings are in line with previous studies which revealed the less problematic profile of Moroccan adolescents in pre-trial arrest in the Netherlands compared to native Dutch adolescents in pre-trial arrest.